Highway pavement structure with low carbon emission and paving method thereof

By using a multi-layer structure and a carbon adsorption layer of solid waste materials in the highway road surface, combined with porous fiber felt and water-based adhesive, the problem of large carbon emissions during asphalt mixture paving is solved, and carbon emission reduction is achieved and The durability of the pavement structure is improved.

CN119243541APending Publication Date: 2025-01-03中电建路桥集团有限公司
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411475405.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-22
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

During the construction of highway road surfaces, especially during the paving process of asphalt mixture, the carbon emissions generated are large and difficult to suppress, and the existing technology has not effectively paid attention to and studied this issue.

Method used

The road surface of the low-carbon emission highway with a multi-layer structure, including the first and second carbon adsorption layers, uses solid waste materials as carbon adsorption materials, forms slurry through water-based adhesives, and sprays on porous fiber felts to form carbon adsorption. The layer is laid between the asphalt layers, combined with porous support to improve carbon adsorption efficiency.

Benefits of technology

It effectively reduces carbon emissions, improves the strength and compressive resistance of the pavement structure, extends the service life of the pavement, reduces construction costs and environmental impacts, and reflects environmental protection and sustainability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119243541A_ABST
    Figure CN119243541A_ABST
Patent Text Reader

Abstract

The invention discloses an expressway pavement structure with low carbon emission and a paving method thereof, which can effectively reduce carbon emission generated by paving an asphalt mixture. The low-carbon-emission expressway pavement structure comprises a first asphalt layer, a second asphalt layer and a third asphalt layer, wherein the first asphalt layer is paved on a soil matrix; the first asphalt layer comprises first particles and asphalt; the first carbon adsorption layer is laid on the first asphalt layer; the first carbon adsorption layer comprises a first porous support body and solid waste slurry attached to the pore surface of the first porous support body; the second asphalt layer is laid on the first carbon adsorption layer; the third asphalt layer is laid on the second asphalt layer; the fourth asphalt layer is laid on the third asphalt layer; the second carbon adsorption layer is paved on the third asphalt layer; wherein the solid waste slurry is slurry formed by a solid waste material capable of adsorbing carbon dioxide in a water-based adhesive.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of highway carbon emission, and in particular to a highway pavement structure with low carbon emission and a paving method thereof. Background Art

[0002] At present, the carbon emissions of highway pavement construction mainly focus on the following processes: (1) Production and transportation of raw materials: carbon emissions from transporting asphalt, cement, sand and gravel and other construction materials from the production site to the construction site. (2) Use of construction equipment: fuel consumption and carbon emissions of large-scale mechanical equipment (such as pavers, rollers, mixers, etc.) used in the construction process. (3) Use of auxiliary materials in the construction process: including the production and use of materials such as additives and curing agents. (4) Transportation and daily activities of construction personnel: carbon emissions from the transportation of construction personnel to and from the construction site, and carbon emissions from temporary facilities (such as sheds, generators, etc.) at the construction site. (5) Waste treatment: carbon emissions from the treatment and transportation of waste generated during the construction process (such as discarded construction materials, packaging, etc.). Among them, most studies focus on improving the production and transportation of raw materials to reduce carbon emissions, for example, selecting alternative materials with lower carbon emissions in the production process, such as cold recycled asphalt mixture, green cement, etc.

[0003] A lot of carbon emissions are also generated during the asphalt paving process, especially the carbon emissions generated by traditional asphalt mixture paving can account for 10% of the entire life cycle emissions. However, due to the large paving area, carbon emissions are difficult to control. Therefore, not much attention and research has been paid to the carbon emissions generated during the asphalt mixture paving process. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a low-carbon emission highway pavement structure and a paving method thereof which can effectively reduce the carbon emission generated by asphalt mixture paving.

[0005] In order to achieve the above object, according to the first aspect of the present invention, a low-carbon emission highway pavement structure is provided, and the technical solution is as follows:

[0006] Low-carbon highway pavement structure, including:

[0007] A first asphalt layer, wherein the first asphalt layer is laid on the soil base; the first asphalt layer comprises first particles and asphalt;

[0008] A first carbon adsorption layer, wherein the first carbon adsorption layer is laid on the first asphalt layer; the first carbon adsorption layer comprises a first porous support and solid waste slurry attached to the pore surface of the first porous support;

[0009] A second asphalt layer, wherein the second asphalt layer is laid on the first carbon adsorption layer; the second asphalt layer comprises a second porous support and second particles and asphalt attached to the pore surface of the second porous support;

[0010] a third asphalt layer, the third asphalt layer being laid on the second asphalt layer; the third asphalt layer comprising second particles and asphalt;

[0011] A fourth asphalt layer, the fourth asphalt layer is laid on the third asphalt layer; the fourth asphalt layer comprises a third porous support and second particles and asphalt attached to the pore surface of the third porous support;

[0012] A second carbon adsorption layer, wherein the second carbon adsorption layer is laid on the third asphalt layer; a fourth porous support body of the second carbon adsorption layer and solid waste slurry attached to the pore surface of the fourth porous support body;

[0013] The solid waste slurry is a slurry formed by solid waste materials that can absorb carbon dioxide in an aqueous adhesive.

[0014] As a further improvement of the above-mentioned low-carbon emission highway pavement structure: the first porous support body and the second porous support body constitute an integrated first porous fiber felt; and / or the third porous support body and the fourth porous support body constitute an integrated second porous fiber felt.

[0015] As a further improvement of the above-mentioned low-carbon emission highway pavement structure: the thickness of the first porous fiber felt and / or the second porous fiber felt is 8 to 20 mm, and the average pore size is 0.5 to 3 mm.

[0016] As a further improvement of the above-mentioned low-carbon emission highway pavement structure: the first porous fiber felt and / or the second porous fiber felt is any one of glass fiber felt, basalt fiber felt, aramid fiber felt, carbon fiber felt, ceramic fiber felt, and polyimide fiber felt.

[0017] As a further improvement of the above-mentioned low-carbon emission highway pavement structure: the solid waste material is at least one of steel slag, fly ash, biomass waste, cement kiln dust, and papermaking sludge powder; the particle size of the solid waste material is 0.2 to 2 mm.

[0018] As a further improvement of the above-mentioned low-carbon emission highway pavement structure: the water-based adhesive is obtained by dissolving at least one of polyvinyl alcohol, polyacrylate, acrylate copolymer, carboxymethyl cellulose, ethylene-vinyl acetate copolymer, and polyurethane in water.

[0019] As a further improvement of the above-mentioned low-carbon emission highway pavement structure: the viscosity of the solid waste slurry is 100-200 mPa·s, and the solid waste slurry is sprayed onto the side of the corresponding porous support body, and the corresponding carbon adsorption layer is obtained after drying.

[0020] As a further improvement to the above-mentioned low-carbon emission highway pavement structure: the thickness of the first carbon adsorption layer and / or the second carbon adsorption layer is 4 to 10 mm.

[0021] As a further improvement of the above-mentioned low-carbon emission highway pavement structure: it also includes a cushion layer and a base layer arranged between the first asphalt layer and the soil base; it also includes a fifth asphalt layer arranged on the second carbon adsorption layer.

[0022] In order to achieve the above object, according to the second aspect of the present invention, a construction method of a highway pavement structure with low carbon emissions is provided, and the technical solution is as follows:

[0023] The construction method of the low-carbon emission highway pavement structure described in the first aspect above comprises the following steps:

[0024] After spraying solid waste slurry on one side of the first porous fiber felt and the second porous fiber felt, drying is performed;

[0025] Spreading a first asphalt mixture on the soil base to form a first asphalt layer;

[0026] After the first asphalt mixture is paved, the first fiber felt with solid waste slurry attached thereto is immediately laid to obtain a first carbon adsorption layer; wherein the side of the first fiber felt with solid waste slurry attached thereto faces downward;

[0027] Spreading a second asphalt mixture on the upper surface of the first fiber felt to which the solid waste slurry is not attached, to obtain a second asphalt layer and a third asphalt layer;

[0028] After the second asphalt mixture is paved, the second fiber felt with solid waste slurry attached thereto is immediately laid to obtain a fourth asphalt layer and a second carbon adsorption layer; wherein the side of the second fiber felt with solid waste slurry attached thereto faces upward.

[0029] It can be seen that the low-carbon emission highway pavement structure and the paving method thereof of the present invention have the following advantages:

[0030] (1) Environmentally friendly: Using solid waste materials that can absorb carbon dioxide as the carbon adsorption layer can effectively reduce carbon dioxide emissions during road construction, reflecting the design concept of low-carbon and environmental protection. Using water-based adhesives instead of traditional solvent-based adhesives can reduce the emission of harmful volatiles, be more environmentally friendly, and improve construction safety.

[0031] (2) Strong sustainability: using industrial waste such as steel slag, fly ash and other solid waste materials asCarbon adsorption material This not only reduces the emission of these solid wastes and prolongs the service life of the road surface, but also reduces the accumulation of these solid wastes and their impact on the environment. By reusing solid waste materials, the cost of raw materials is reduced. Procurement costs , while reducing waste disposal costs and having good economic benefits.

[0032] (3) Excellent structural performance: A porous support such as porous fiber felt is used to carry and fix the adjacent asphalt layer and carbon adsorption layer materials. The asphalt layer can penetrate into the gaps in the porous support, so that the multi-layer asphalt layer is combined with the carbon adsorption layer. Improved the strength and compression resistance of the pavement structure , which can effectively resist the impact of traffic load and climate change. At the same time, the porous structure of the porous support makes it have a large specific surface area, which is conducive to the attachment and fixation of carbon adsorption materials, and can provide a large carbon adsorption area, thus improving Carbon adsorption efficiency .

[0033] (4) Convenient construction: The pavement structure is simple in structure and is completed through simple spraying and paving steps. It does not require complicated processes and is easy to construct. The process is simple and convenient for construction operations and quality control.

[0034] It can be seen that the low-carbon emission highway pavement structure and its paving method of the present invention integrate solid waste utilization, new technology and environmental protection concepts. It not only has significant advantages in environmental protection, but also can improve the durability of the pavement structure and reduce construction costs. It is an innovative highway pavement structure solution with broad application prospects.

[0035] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments. Additional aspects and advantages of the present invention will be partially given in the following description, partially become apparent from the following description, or be learned through the practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] The drawings constituting a part of the present invention are used to assist in understanding the present invention. The contents provided in the drawings and their related descriptions in the present invention can be used to explain the present invention, but do not constitute improper limitations on the present invention. In the drawings:

[0037] Figure 1 It is a schematic structural diagram of the low-carbon emission highway pavement structure of the present invention.

[0038] Figure 2 This is a partial enlarged view of the low-carbon emission highway pavement structure of the present invention.

[0039] Figure 3 It is a schematic flow chart of an embodiment of the construction method of a low-carbon emission highway pavement structure of the present invention.

[0040] The relevant marks in the above drawings are:

[0041] 110 - first asphalt layer, 120 - second asphalt layer, 130 - third asphalt layer, 140 - fourth asphalt layer, 210 - first carbon adsorption layer, 220 - second carbon adsorption layer, 150 - fifth asphalt layer, 310 - first porous support, 320 - second porous fiber felt, 410 - cushion layer, 420 - base layer. DETAILED DESCRIPTION

[0042] The present invention is described clearly and completely below in conjunction with the accompanying drawings. A person skilled in the art will be able to implement the present invention based on these descriptions. Before describing the present invention in conjunction with the accompanying drawings, it should be particularly noted that:

[0043] The technical solutions and technical features provided in each part of the present invention, including the following description, may be combined with each other if there is no conflict.

[0044] In addition, the embodiments of the present invention involved in the following description are generally only a part of the embodiments of the present invention, rather than all the embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.

[0045] About the terms and units in the present invention: The terms "include", "have" and any variations thereof in the description and claims of the present invention and related parts are intended to cover non-exclusive inclusions.

[0046] Figure 1 It is a schematic structural diagram of the low-carbon emission highway pavement structure of the present invention. Figure 2 This is a partial enlarged view of the low-carbon emission highway pavement structure of the present invention ( Figure 1 (enlarged view of point A in the middle).

[0047] like Figure 1-2As shown, the low-carbon emission highway pavement structure includes a cushion layer 410, a base layer 420, a first asphalt layer 110, a first carbon adsorption layer 210, a second asphalt layer 120, a third asphalt layer 130, a fourth asphalt layer 140, a second carbon adsorption layer 220 and a fifth asphalt layer 150, which are sequentially arranged on the soil base. The first asphalt layer 110 is laid on the soil base, and the first asphalt layer 110 includes first particles and asphalt. The first carbon adsorption layer 210 is laid on the first asphalt layer 110, and the first carbon adsorption layer 210 includes a first porous support 310 and solid waste slurry attached to the pore surface of the first porous support 310. The second asphalt layer 120 is laid on the first carbon adsorption layer 210, and the second asphalt layer 120 includes a second porous support and second particles and asphalt attached to the pore surface of the second porous support. The third asphalt layer 130 is laid on the second asphalt layer 120, and the third asphalt layer 130 includes second particles and asphalt. The fourth asphalt layer 140 is laid on the third asphalt layer 130, and the fourth asphalt layer 140 includes a third porous support and second particles and asphalt attached to the pore surface of the third porous support. The second carbon adsorption layer 220 is laid on the third asphalt layer 130, and the second carbon adsorption layer 220 includes a fourth porous support and solid waste slurry attached to the pore surface of the fourth porous support. The fifth asphalt layer 150 is laid on the second carbon adsorption layer 220, and the fifth asphalt layer 150 includes third particles and asphalt.

[0048] The solid waste slurry is a slurry formed by solid waste materials that can absorb carbon dioxide in an aqueous adhesive.

[0049] Preferably, the solid waste material is at least one of steel slag, fly ash, biomass waste, cement kiln dust, and papermaking sludge powder. Calcium oxide (CaO) and magnesium oxide (MgO) in steel slag can react with carbon dioxide under appropriate conditions to generate calcium carbonate (CaCO 3 ) and magnesium carbonate (MgCO 3 ), thereby achieving the mineralization and adsorption of carbon dioxide. Fly ash contains a large amount of silicates and aluminates, which can react with carbon dioxide to form carbonate compounds under certain conditions. Biochar generated by pyrolysis and carbonization of biomass waste has a porous structure and can physically adsorb carbon dioxide. Cement kiln ash contains a high amount of alkaline components (such as calcium oxide), which can react with carbon dioxide to form stable carbonates. Papermaking sludge contains a large amount of cellulose and calcium components, which can adsorb carbon dioxide under certain conditions, especially through the carbonization process.

[0050] Preferably, the particle size of the solid waste material is 0.2 to 2 mm, which has the following advantages: it can ensure a more uniform distribution during the mixing process, avoiding unstable material properties caused by inconsistent particle size; it can provide a better inter-particle embedding effect, thereby improving the mechanical properties of the material, such as compressive strength and shear strength; it has a larger specific surface area, which helps to improve the adsorption capacity and reaction activity of the material, thereby enhancing the carbon adsorption effect; it can form a better interface bonding with asphalt and improve the overall performance of the composite material; it can better fill the gaps and reduce the porosity during the compaction process, thereby improving the density and durability of the material; it can ensure that the solid waste material generates less dust and particles during the processing and application process, reducing pollution to the environment; it is easier to produce through conventional screening and crushing equipment, reducing processing costs and improving economic benefits.

[0051] Preferably, the aqueous adhesive is obtained by dissolving at least one of polyvinyl alcohol, polyacrylate, acrylate copolymer, carboxymethyl cellulose, ethylene-vinyl acetate copolymer, and polyurethane in water; these materials are environmentally friendly, have good dispersibility and suitable viscosity in water bodies, and the solid waste slurry formed has good uniformity, forms a uniform film layer after drying, and performs well under high temperature conditions of asphalt paving.

[0052] Preferably, the viscosity of the solid waste slurry is 100-200 mPas, and the solid waste slurry is sprayed onto the side of the corresponding porous support, and the corresponding carbon adsorption layer is obtained after drying. Among them, setting the viscosity of the solid waste slurry to 100-200 mPas has the following advantages: it has appropriate fluidity, is not too thin to cause flow, and is not too viscous to be difficult to handle. It can be easily pumped and sprayed during the construction process to ensure smooth construction and uniform coverage; it helps the solid waste slurry to penetrate into the pores of the porous support, improve the bonding strength between the solid waste slurry and the porous support, reduce the risk of falling off and delamination, and thus increase the overall stability and durability of the pavement structure; it helps to reduce the formation of bubbles during the slurry curing process, thereby reducing the porosity of the material and improving its density and mechanical properties; after curing, it can form a dense solid structure, improve the compressive strength, shear strength and durability of the material, and extend the service life of the pavement.

[0053] The first porous support 310 and the second porous support constitute an integrated first porous fiber felt, and the third porous support and the fourth porous support constitute an integrated second porous fiber felt 320. Thus, the integrated structure can better disperse and withstand external pressure and reduce local stress concentration; at the same time, the asphalt layer can penetrate into the pores of the porous fiber layer, reducing the displacement and deformation that may occur between independent supports, and improving the durability and reliability of the entire pavement structure.

[0054] Preferably, the thickness of the first porous support 310 and the second porous fiber felt 320 is 8-20 mm, the average pore size is 0.5-3 mm, and the thickness of the first carbon adsorption layer 210 and / or the second carbon adsorption layer 220 is 4-10 mm. Thus, the contact thickness between the porous fiber felt and the asphalt can be made appropriate on the basis of ensuring a good carbon adsorption effect, and the connection strength between the layers can be ensured.

[0055] Preferably, the first porous support 310 and the second porous fiber felt 320 are any one of glass fiber felt, basalt fiber felt, aramid fiber felt, carbon fiber felt, ceramic fiber felt, and polyimide fiber felt. These porous fiber felts have low cost, good high temperature resistance, and can withstand the high temperature of asphalt mixture, and high strength, which can provide durability of the pavement structure.

[0056] The above-mentioned asphalt layers are composed of different asphalts and particles, wherein the first asphalt layer 110 uses ordinary asphalt mixture, and the first particles include coarse aggregates with larger particle sizes such as quartz sand, crushed stone, etc.; the second asphalt layer 120, the third asphalt layer 130 and the fourth asphalt layer 140 use ordinary asphalt mixture, and the second particles include coarse aggregates with larger particle sizes such as limestone, basalt, etc.; the fifth asphalt layer 150 uses modified warm-mix asphalt mixture, cold-mix asphalt mixture or foamed asphalt, and the third particles include coarse aggregates with smaller particle sizes such as granite, limestone, etc. The total thickness of the first asphalt layer 110 to the fifth asphalt layer 150 is 15 to 30 cm.

[0057] The cushion layer 410 is made of a mixture of natural sand and gravel, with a thickness of 30 to 50 cm, and has good drainage and bearing performance. The base layer 420 is paved with graded crushed stone, with a thickness of 40 to 60 cm, and has high strength and stability, and can bear the upper load and transfer it to the lower structure.

[0058] Figure 3 The figure is a schematic flow chart of an embodiment of a construction method for a low-carbon emission highway pavement structure according to the present invention.

[0059] like Figure 3 As shown, the construction method of the low-carbon emission highway pavement structure includes the following steps:

[0060] After spraying solid waste slurry on one side of the first porous fiber felt and the second porous fiber felt 320, drying is performed;

[0061] Reference Figure 3 (a) spreading a first asphalt mixture on the soil base on which the cushion layer 410 and the base layer 420 have been laid to form a first asphalt layer 110;

[0062] Reference Figure 3(b) immediately after the first asphalt mixture is paved, a first fiber felt with solid waste slurry attached thereto is laid to obtain a first carbon adsorption layer 210; wherein the side of the first fiber felt with solid waste slurry attached thereto faces downward;

[0063] Reference Figure 3 (c) spreading a second asphalt mixture on the upper surface of the first fiber felt to which the solid waste slurry is not attached, to obtain a second asphalt layer 120 and a third asphalt layer 130;

[0064] Reference Figure 3 (d) After the second asphalt mixture is paved, the second fiber felt with solid waste slurry attached thereto is immediately laid to obtain a fourth asphalt layer 140 and a second carbon adsorption layer 220; wherein the side of the second fiber felt with solid waste slurry attached thereto faces upward.

[0065] Reference Figure 3 (e) Laying the fifth asphalt layer 150 on the second carbon adsorption layer 220, the construction is completed.

[0066] The test blocks of the above-mentioned highway pavement structure were prepared, and the test blocks were subjected to multiple cyclic loading tests using the asphalt mixture four-point bending fatigue life tester of Cangzhou Taiding Hengye Testing Instrument Co., Ltd. The test results show that the fatigue life of the test blocks is more than 1,200,000 loading cycles. The test blocks were subjected to compression tests using the asphalt mixture uniaxial compression test (cylinder method) of Cangzhou Taiding Hengye Testing Instrument Co., Ltd., and the test results show that the compressive strength of the test blocks is ≥75MPa.

[0067] The above is a description of the relevant contents of the present invention. A person skilled in the art will be able to implement the present invention based on these descriptions. Based on the above contents of the present invention, all other embodiments obtained by a person skilled in the art without creative work shall fall within the scope of protection of the present invention.

Claims

1. A low-carbon emission highway pavement structure, characterized by: include: A first asphalt layer (110), wherein the first asphalt layer (110) is laid on a soil base; the first asphalt layer (110) comprises first particles and asphalt; A first carbon adsorption layer (210), wherein the first carbon adsorption layer (210) is laid on the first asphalt layer (110); the first carbon adsorption layer (210) comprises a first porous support (310) and a solid waste slurry attached to the pore surface of the first porous support (310); A second asphalt layer (120), wherein the second asphalt layer (120) is laid on the first carbon adsorption layer (210); the second asphalt layer (120) comprises a second porous support and second particles and asphalt attached to the pore surface of the second porous support; A third asphalt layer (130), the third asphalt layer (130) being laid on the second asphalt layer (120); the third asphalt layer (130) comprising second particles and asphalt; A fourth asphalt layer (140), the fourth asphalt layer (140) being laid on the third asphalt layer (130); the fourth asphalt layer (140) comprising a third porous support and second particles and asphalt attached to the pore surface of the third porous support; A second carbon adsorption layer (220), wherein the second carbon adsorption layer (220) is laid on the third asphalt layer (130); the second carbon adsorption layer (220) comprises a fourth porous support and a solid waste slurry attached to the pore surface of the fourth porous support; The solid waste slurry is a slurry formed by solid waste materials that can absorb carbon dioxide in an aqueous adhesive.

2. The low-carbon emission highway pavement structure according to claim 1, characterized in that: The first porous support (310) and the second porous support constitute an integrated first porous fiber felt; and / or the third porous support and the fourth porous support constitute an integrated second porous fiber felt (320).

3. The low-carbon emission highway pavement structure according to claim 2, characterized in that: The first porous fiber felt and / or the second porous fiber felt (320) has a thickness of 8 to 20 mm and an average pore size of 0.5 to 3 mm.

4. The low-carbon emission highway pavement structure according to claim 2, characterized in that: The first porous fiber felt and / or the second porous fiber felt (320) is any one of glass fiber felt, basalt fiber felt, aramid fiber felt, carbon fiber felt, ceramic fiber felt, and polyimide fiber felt.

5. The low-carbon emission highway pavement structure according to claim 1, characterized in that: The solid waste material is at least one of steel slag, fly ash, biomass waste, cement kiln dust, and papermaking sludge powder; the particle size of the solid waste material is 0.2-2 mm.

6. The low-carbon emission highway pavement structure according to claim 1, characterized in that: The water-based adhesive is obtained by dissolving at least one of polyvinyl alcohol, polyacrylate, acrylate copolymer, carboxymethyl cellulose, ethylene-vinyl acetate copolymer and polyurethane in water.

7. The low-carbon emission highway pavement structure according to claim 1, characterized in that: The viscosity of the solid waste slurry is 100-200 mPas. The solid waste slurry is sprayed onto the side of the corresponding porous support body, and the corresponding carbon adsorption layer is obtained after drying.

8. The low-carbon emission highway pavement structure according to claim 1, characterized in that: The thickness of the first carbon adsorption layer (210) and / or the second carbon adsorption layer (220) is 4 to 10 mm.

9. The low-carbon emission highway pavement structure according to claim 1, characterized in that: It also includes a cushion layer (410) and a base layer (420) arranged between the first asphalt layer (110) and the soil base; and a fifth asphalt layer (150) arranged on the second carbon adsorption layer (220).

10. The construction method of a low-carbon emission highway pavement structure according to any one of claims 1 to 9, characterized in that: Includes steps: Spraying solid waste slurry on one side of the first porous fiber felt and the second porous fiber felt (320) and then performing a drying process; Spreading a first asphalt mixture on the soil base to form a first asphalt layer (110); Immediately after the first asphalt mixture is paved, a first fiber felt with solid waste slurry attached thereto is laid to obtain a first carbon adsorption layer (210); wherein the side of the first fiber felt with solid waste slurry attached thereto faces downward; Spreading a second asphalt mixture on the upper surface of the first fiber felt to which the solid waste slurry is not attached, to obtain a second asphalt layer (120) and a third asphalt layer (130); After the second asphalt mixture is paved, the second fiber felt with solid waste slurry attached is immediately laid to obtain a fourth asphalt layer (140) and a second carbon adsorption layer (220); wherein the side of the second fiber felt with solid waste slurry attached faces upward.